2014
DOI: 10.1007/s13197-014-1319-5
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and purification of wheat-esterase using aqueous two-phase systems of ionic liquid and salt

Abstract: To explore a new and simple rapid extraction and purification technique for wheat-esterase, an ionic liquids (ILs)-based aqueous two-phase system (ATPS) was developed for the purification of wheat-esterase from wheat extracts. Effects of various process parameters such as the concentrations of [Bmim]BF 4 , the types and concentrations of phaseforming salt, the system pH and the temperature on partitioning of wheat-esterase were evaluated. The obtained data indicated that wheat-esterase was preferentially parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 26 publications
1
27
0
1
Order By: Relevance
“…The few studies reported on esterase purification by ATPS are focused on esterases from plant origin. Jiang, Feng, Liu, Xu, Li and Ji [50] explored the purification of wheat-esterase using ionic liquids-based ATPSs. Under optimum conditions (20% (w/w) of 1-Butyl-3-methylimidazolium tetrafluoroborate and 25% (w/w) of NaH 2 PO 4 pH 4.8), the enzyme was obtained with a purification factor of 4.2 and a recovery yield of 89%.…”
Section: Partial Purification Of Esterasementioning
confidence: 99%
“…The few studies reported on esterase purification by ATPS are focused on esterases from plant origin. Jiang, Feng, Liu, Xu, Li and Ji [50] explored the purification of wheat-esterase using ionic liquids-based ATPSs. Under optimum conditions (20% (w/w) of 1-Butyl-3-methylimidazolium tetrafluoroborate and 25% (w/w) of NaH 2 PO 4 pH 4.8), the enzyme was obtained with a purification factor of 4.2 and a recovery yield of 89%.…”
Section: Partial Purification Of Esterasementioning
confidence: 99%
“…100% recovery of Bovine serum albumin is reported using phosphonium and ammonium-based ILs [22]. 1-Butyl-3-methylimidazolium tetrafluoroborate based ILs enabled the preferential partitioning of wheat esterase from wheat extracts towards ILs rich phase with a recovery of 88.93% [23].The practical advantage of tailoring the ionic liquids enabled even for the separation of enantiomers of aminoacids from racemic mixture [24]. In a study to understand the driving forces influencing extraction by ionic liquids, electrostatic interaction between surface charged residues of aminoacids and positive charge of cation of ionic liquid is determined to be the most prominent [25].…”
Section: G Ionic Liquids In Atps Based Extractionmentioning
confidence: 99%
“…The aqueous biphasic system (ABS) is recognized as an environmentally friendly method, as an alternative to the traditional LLE, since both phases of the ABS are aqueous solutions, and it could be used for organic compounds [1][2][3][4][5] and biological macromolecule [6][7][8][9] extractions without using any volatile organic solvent. Up to now, ABS could be composed of polymer and salt, polymer and polymer, ionic liquid (IL) and polymer, IL and salt, IL and surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…Among these factors, the effect of pH value of salt solution on the ABS formation should not be ignored. Its influence on the protein extraction by ABSs [7,9,[23][24][25][26][27][28][29][30] was fully investigated, since the pH value could affect the electrostatic interaction and hydrophobic interaction in the target proteins extraction, and then influence their extraction recoveries. However, its effect on the formation of ABS by cholinium-based IL and salt was scarcely studied [22], since it is relatively difficult to create the cholinium IL-based ABSs by salts.…”
Section: Introductionmentioning
confidence: 99%